DIMINISHING OF TRUE POWER LOSS BY APIDAE ALGORITHM - Lenin, K. (International Journal of Research -GRANTHAALAYAH, 2018)
In this paper, Apidae Algorithm (AA) is proposed for solving reactive power problem. Apidae Algorithm, inspired from the natural foraging behaviour of Apidae, & it has been utilized to solve the reactive power problem. The AA algorithm carry out the intensified neighbourhood search united with a random mode exploration search. Efficiency of the projected Apidae Algorithm (AA) is validated by evaluating in standard IEEE 118, 300 bus test systems. Simulated outcomes shows that active power loss has been reduced with variables are within the limits.